2010
DOI: 10.1128/jb.00176-10
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Competitiveness of Two Natural Variants of the IncQ-Like Plasmids, pRAS3.1 and pRAS3.2

Abstract: Plasmids pRAS3.1 and pRAS3.2 are natural variants of the IncQ-2 plasmid family, that except for two differences, have identical plasmid backbones. Plasmid pRAS3.1 has four 22-bp iterons in its oriV region, while pRAS3.2 has only three 6-bp repeats and pRAS3.1 has five 6-bp repeats in the promoter region of the mobB-mobA/repB genes and pRAS3.2 has only four. In previous work, we showed that the overall effect of these differences was that when the plasmid was in an Escherichia coli host, the copy numbers of pRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Iterons were the major incompatibility determinants in IncQ plasmids, so point mutations within the three 20-bp conserved repeats of iterons could result in an inability or significantly reduced ability to exert incompatibility, initiate replication, or transfer genes by conjugation [ 43 ]. Meanwhile, the iteron number had a negative effect on plasmid copy number, as well as the antibiotic resistance level, and imposed metabolic burden [ 44 ]. Hence, variations in the iteron sequence may reflect the need for balance between high antibiotic resistance and a stable existence [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iterons were the major incompatibility determinants in IncQ plasmids, so point mutations within the three 20-bp conserved repeats of iterons could result in an inability or significantly reduced ability to exert incompatibility, initiate replication, or transfer genes by conjugation [ 43 ]. Meanwhile, the iteron number had a negative effect on plasmid copy number, as well as the antibiotic resistance level, and imposed metabolic burden [ 44 ]. Hence, variations in the iteron sequence may reflect the need for balance between high antibiotic resistance and a stable existence [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like pRAS3.1 and pRAS3.2, pRAS3.3 has the same two ORFs that code for an active toxin-antitoxin system related to the PemK/ Mazf family (32,33).…”
Section: Resultsmentioning
confidence: 99%
“…27 Another study found that an IncQ plasmid has evolved to a lower copy number variant; this variant is more competitive within the bacterial population than a higher copy number variant because it places a lower metabolic load on the bacterial host. 28 Likewise, transfer of the symbiotic plasmid from the β-rhizobium Cupriavidus taiwanensis to the taxonomically related plant pathogen Ralstonia solanacearum allowed the adaptive evolution of the latter, after the inactivation of the T3SS by a single or a double mutation, into a nodulating symbiont. 29 Although these data resulted from artificial evolution settings, the experiments underscore the amazing plasticity of bacteriaplasmid associations and the potential for rapidly generating new phenotypes.…”
Section: The Influence Of the Accessory Genome On Bacterial Pathogen mentioning
confidence: 99%